Domestic Terrorism and Sovereign Bond Ratings in the Developing World - Biglaiser, Glen (Terrorism and political violence, 2023)
Since the 1990s, credit rating agencies have played a prominent financial role in developing countries, rating their sovereign bonds and determining capital costs. Over much the same years, domestic terrorism has expanded, increasing market disruptions in countries. Despite the heightened costs related to rebel attacks, few studies investigate the impact of domestic terrorism on bond ratings. Using a sample of seventy-one developing countries between 1996 and 2018, we find that domestic terrorist incidents result in sovereign bond downgrades for countries that receive ratings. Further, when we disaggregate terrorist events by target type, we observe that attacks directed at the government, military and police, business, non-governmental organizations, and private citizens/property have a larger effect than other terrorist incidents. We argue that specific domestic terrorist attacks increase economic instability, leading to capital flight, and a shifting of resources from productive economic sectors to counterterrorism. The resulting economic changes weaken a country’s economy and increase debt nonpayment risk.